Al Karamu fī Syi’ri ‘Urwa Ibn Al-Ward (Dirāsatun Waṣfiyyatun Taḥlīliyyatun) - Haruna, Haruna Abubakar (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
This paper: the generosity in the urwa ibn war'd poetry descriptive-analytical study. contains the nobility of humanity in the urwa's of saalik poetry, the paper also concentrates on urwa's generosity and liberality, it contains four major points, the first point is about the theoretical framework-the concept of generosity which is openhandedness, giving and feeding nicely. the second point is generosity between jahiliyyah and Islam, thus, we realized it's the role and wonderful impact in the Arab societies, even though generosity become the link for collaboration between ethic groups of Arab poor and wealthy people through social activities. it also discusses about the personality of urwa in the third and fourth point of the paper describing his popularity, nobility, and knighthood, the urwa ibn war'd listed among the most remarkable people, loved and influential hero in the jahiliyyah period. thus, he's the best of his kind and open-handedness to poor, leniency and sympathy to weakly handicaps, and daily favor to patients. impact the urwa assemble all sense of honor and specifications of generosity, donations, courage, chastity and nobility, right protection, impact he become honorable and he promoted (saalaka) and convert it to nobility.